2004
DOI: 10.1248/bpb.27.1788
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of DY-9760e, a Calmodulin Antagonist, against Neuronal Cell Death

Abstract: An excessive elevation of intracellular Ca2؉ levels is known to play a key role in the pathological events following cerebral ischemia. DY-9760e, 3-[2-[4-(3-chloro-2-methylphenylmethyl)-1-piperazinyl]ethyl]-5,6-dimethoxy-1-(4-imidazolylmethyl)-1H-indazole dihydrochloride 3.5 hydrate, is a potent calmodulin antagonist that attenuates brain damage in focal ischemia models. In the present study, we investigated the effect of DY-9760e on neuronal cell death induced by a variety of cell-toxic stimuli that increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…Treatment with DY-9760e, a calmodulin antagonist, resulted in a dosedependent prevention of neuronal cell death elicited by excitotoxicity, voltage-gated channel opening, and inhibition of ER Ca 2? ATPase [173]. Although the mode of cell death and underlying mechanisms are not yet clear, CaMK-II that is regulated by calcium has been shown to induce ERK activation in neurons and vascular smooth muscle cells [174,175].…”
Section: Protein Kinasesmentioning
confidence: 99%
“…Treatment with DY-9760e, a calmodulin antagonist, resulted in a dosedependent prevention of neuronal cell death elicited by excitotoxicity, voltage-gated channel opening, and inhibition of ER Ca 2? ATPase [173]. Although the mode of cell death and underlying mechanisms are not yet clear, CaMK-II that is regulated by calcium has been shown to induce ERK activation in neurons and vascular smooth muscle cells [174,175].…”
Section: Protein Kinasesmentioning
confidence: 99%
“…30) Therefore, there are strong clinical demands for neuroprotective agents that can block neuronal death associated with stroke. 31) We have developed DY-9760e, a calmodulin antagonist, which exerts neuroprotective action against cell death induced by Ca 2ϩ overload 15,17) and ameliorates brain injury that occurs after cerebral ischemia in rodents. [18][19][20][21][22]32,33) The present study demonstrates that DY9760e reduces the infarct volume in cats with permanent MCA occlusion, and this finding is consistent with previous studies in rats with permanent MCA occlusion, extending the observation into a gyrencephalic species.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, DY-9760e can rescue neurons from cell death elicited by cell-toxic stimuli that mimic cellular events observed in cerebral ischemia. 15,17) In addition, it has been shown that trifluoperazine, a calmodulin antagonist that is structurally different from DY-9760e, attenuates brain injury after transient MCA occlusion without improving CBF. 43) Taken together, these results indicate that the neuroprotection demonstrated in animal models may be due to a direct action of DY-9760e in the brain parenchyma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations